Brinjal (Solanum melongena) Fruit Yield in Response to Urea Super Granule Application - Hussain, MJ; Ali, MY; Rahman, MM; Quayyum, MA; Choudhury, DA (The Agriculturists, 2010)
Experiments were conducted to assess the effects of USG on the number of branch and fruit production, fruit length, weight and yield of brinjal (Solanum melongena: cv Shingnath), compared to prilled urea as N source. The study was conducted at farming systems research and development site, Palima, Tangail district under AEZ 8 of Bangladesh during 2000, 2001 and 2002 using randomized complete block design (RCBD) with five treatments replicated 6 times. The treatments were T1= N78P36K66S17CD3t (Recommended dose for high yield goal (HYG), N as prilled urea), T2= N78P36K66S17CD3t (Recommended dose for HYG, N as USG), T3= N65P36K66S17CD3t (N 10%< Recommended dose as USG), T4= N52P36K66S17CD3t (N 20%<Recommended dose as USG) and T5 = N60P35K60S0CD5t (Farmers dose, N as Prilled urea). USG had significant (P?0.05) effect on the brinjal fruit yield giving higher profits. Thus USG as N78P36K66S17CD3t was beneficial for brinjal cultivation in terms of yield and economics.